Pelaksanaan Hypnobreastfeeding sebagai Upaya Menurunkan Tingkat Kecemasan Ibu Menyusui - Suci Sulistyorini; Deby Meitia Sandy (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Breastfeeding problems are not only related to the amount of breast milk produced. Psychological factors play an important role in the breastfeeding process. Breastfeeding mothers often experience anxiety due to a lack of knowledge about caring for themselves and their babies (Walyani, 2015). The Indonesian Ministry of Health report (2016) stated that 83.4% of breastfeeding mothers experienced severe anxiety and 16.6% of moderate anxiety, while multiparous mothers experienced 7% of severe anxiety, 71.5% of moderate anxiety and 21.5% mild anxiety. .5%. The aim of the activity is to provide relaxation with hypnobreastfeeding therapy so that it can reduce anxiety in breastfeeding mothers. Method: activities are carried out by providing motivation and positive affirmation sentences through hypnobreastfeeding, music therapy and aromatherapy. Anxiety assessment uses the Depression Anxiety Stress Scales (DASS 42) anxiety scale questionnaire. Results: The average anxiety score of breastfeeding mothers before hypnobreastfeeding was 40.2 or included in the severe stress category and the average anxiety level after hypnobreastfeeding was 28.9 or included in the mild stress category. These results indicate a reduction in stress levels in breastfeeding mothers by 11.3. It is hoped that breastfeeding mothers will maintain their psychological and physical health during the breastfeeding process.